2002
DOI: 10.1002/cbf.954.abs
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that glutamine is involved in neutrophil function

Abstract: Phosphate-dependent glutaminase (PDG) activity, a key enzyme of glutamine metabolism, was determined in neutrophils obtained from the intra-peritoneal cavity (PC) or bronchoalveolar space (BAS) after administration of 1 ml or 100 microl, respectively of saline, glycogen solution (1%) or lipopolysaccharide (LPS 0.1 mg (100 microl)(-1)). Neutrophils were obtained by lavage of both sites with 20 ml saline 24 h after the administration of the stimuli. Glycogen and LPS, depending on the site the cells were obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…27 Glutamine upregulates the expression of the components of NADPH oxidase complex in rat neutrophils. 28 These findings explain the fact that glutamine enhances the bactericidal function of neutrophils from normal patients and those suffering from burns. [1][2][3] Recently, we have found that glutamine delays the onset of apoptosis in rat and human neutrophils.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…27 Glutamine upregulates the expression of the components of NADPH oxidase complex in rat neutrophils. 28 These findings explain the fact that glutamine enhances the bactericidal function of neutrophils from normal patients and those suffering from burns. [1][2][3] Recently, we have found that glutamine delays the onset of apoptosis in rat and human neutrophils.…”
Section: Resultsmentioning
confidence: 91%
“…[1][2][3] Recently, we have found that glutamine delays the onset of apoptosis in rat and human neutrophils. [28][29] Since glutamine metabolism provides NADPH/NADH to maintain the redox state of the cells and to ensure the production of ATP and intermediates for the synthesis of macromolecules such as nucleic acids and lipids, 30 a high glutamine consumption could be a metabolic attempt to preserve the integrity and function of the cells. 11,29 A moderate decrease in ATP level leads to apoptosis whereas a marked decrease of this nucleotide causes necrosis.…”
Section: Resultsmentioning
confidence: 99%
“…The cell suspension was centrifuged at 4 C (500 g for 10 min). The number of viable cells (>95% neutrophils) was determined in a Neubauer chamber under an optical microscope by Trypan blue exclusion (Pires de Melo et al 1998, Pithon-Curi et al 2002.…”
Section: Methodsmentioning
confidence: 99%
“…39 The production of TNF-was shown to be reduced by glutamine (2 mM) in cultured neutrophils stimulated with LPS. 41 Glutamine at concentrations of 4 and 10 mM leads to significant reduction of TNFexpression and release after lipopolysaccharide (LPS) treatment in cultured mononuclear cells. 42 This effect of glutamine treatment was accompanied by stimulated expression of HSP 72 in a dose-dependent fashion.…”
Section: Leukocytesmentioning
confidence: 99%